Espacialização e análise dos registros de fauna do golfão maranhense nos últimos 300 anos e sua correlação com uso e ocupação do solo - GUTERRES, Camila Everton (2022)
In view of the profound changes seen in recent years in land use and occupation, the scientific academy has guided studies on the correlation between anthropic interventions in the landscape with the impacts caused to the functioning of natural systems and consequent loss of biodiversity. Due to the decrease in these environments and the threat to biodiversity, this study intends to map the records of different faunal groups for the Golfão Maranhense - GM region, in order to demonstrate the places less covered by scientific research and evaluate the evolution of the land use and occupation correlating it with the fauna mapped for the GM. Data from fauna records that supported the analysis of this research were collected in a secondary way, through consolidated fauna databases, and spatialized through the GIS QGIS. The records were correlated with the categories of land use and occupation using the MAPBIOMAS platform. The results point to a concentration of studies in the north of the Maranhense Gulf, and the loss of vegetated/natural areas by areas associated with agriculture and livestock activities and urbanization, making forest formations increasingly fragmented, a scenario considered negative because the fragmentation directly impacts the balanced life of the fauna. Mammals were sensitive to the advance of urbanization since their records showed a negative correlation with the increase in area of this use category. Fish and reptiles showed a positive correlation with forest formation and the greater presence of mangroves. The presence of forest formation, as well as rivers, lakes and oceans were important conditions for greater Shannon diversity and Margalef richness. In general, the results demonstrated the sensitivity of different faunal groups to changes in land use and occupation that have historically occurred in the GM region. Therefore, there is a need to encourage research on different faunal groups, through funding notices, to sectors on the east-west contour of the Gulf, at the same time it brings a warning so that research whose methodological proposals result in in the capture of species, that these records can be deposited in official databases, such as Sisbio, SiBBr, among others, in order to facilitate holistic and integrative approaches on the relationship of different faunal groups with anthropic interventions, and, with this, the information can be better incorporated to the possible actions of ecological restoration and conservation biology of the GM.